Integrating Spiritual Values and Social Attitudes in the Traditional Communication Media of Kampung Naga's Indigenous Community - Toteng Suhara; Ilim Abdul Halim (UIN Sunan Gunung Djati Bandung, 2026)
This study analyzes the integration patterns of spiritual values and social attitudes manifested through traditional communication media in the Kampung Naga Indigenous Community, Tasikmalaya. As a community that remains steadfast in upholding ancestral traditions, the Kampung Naga community utilizes various forms of traditional communication, such as the advice of elders, the Hajat Sasih ritual, taboos, oral stories, village spatial structures, and the practice of mutual cooperation as the primary instruments for passing on cultural values. The results of the study indicate that spiritual values, including respect for God and ancestors, a cosmological understanding of the interconnectedness of humans with nature, and the principles of simple living, are directly integrated with social values through collective rituals, customary rules, and daily interactions. Each form of communication not only conveys spiritual teachings but also shapes social ethics, strengthens solidarity, and maintains order in communal life. This consistent integration creates a harmonious, disciplined, and togetherness-filled lifestyle, while demonstrating the Kampung Naga community's efforts to maintain its cultural identity and ancestral values from generation to generation. Thus, this study confirms that traditional communication has a fundamental role in maintaining the continuity of spiritual and social values, and is the main foundation for the formation of social cohesion and cultural sustainability in the Kampung Naga Indigenous community.